Pengembangan Modul Matematika dengan Pendekatan Science, Technology, Engineering, And Mathematics (STEM) pada Materi Segiempat - Utami, Taza Nur; Jatmiko, Agus; Suherman, Suherman (Universitas Islam Negeri Raden Intan Lampung, 2018)
This study aims to determine the feasibility of mathematical modules with STEM approach and the response of learners and teachers to the attractiveness of the module. The research and development procedure used is the Borg and Gall development model modified by sugiyono. The data collection instruments used are questionnaires given to experts to know the feasibility of the products and questionnaires given to learners and teachers to know the attractiveness of the product. The results of the study indicate that the assessment of the experts is very reasonable (87% of material experts, 89% of media experts and 92% of linguists), the response of learners and teachers is very interesting (89% small group trial, 87% field trials and 90% teacher test).